Optimum Height and Tilt Angle of the Solar Receiver for a 30 kWe Solar Tower Power Plant for the Electricity Production in the Sahelian Zone. (22nd July 2021) - Faye, Kory; Thiam, Ababacar; Faye, Mactar
Abstract : This work investigated the prediction of the optimum height and tilt angle of the solar receiver of a 30 kWe solar tower power plant for the electricity production in the Sahelian zone. Initially, the solar field is sized to determine the total reflecting surface area of the mirrors and the number of heliostats. A PS10-like radially staggered heliostat field is used to design the heliostat layout in the field using a Matlab code. The concentrated solar flux at the input of the receiver was determined using Soltrace software by the Monte Carlo ray tracing (MCRT) method. The sizing results show that the total reflecting surface area is 350 m 2 for an optical efficiency of 76.4% and a reference DNI of 600 W/m 2 . The solar field layout indicates 175 heliostats of 2 m 2 surface area and 1.5 m height each. The simulation results show that the optimum height and tilt angle of the solar receiver are 26 m and 65°, respectively.